Delayed Ocular Complications of Mustard Gas on 500 Veterans - Mohammad Reza Ghasemi-Broumand; Zohreh Amiri (University of Social Welfare and Rehabilitation Sciences, 2007)
Objective: Considering the late complications of eye due to mustard gas in warfare patients, this study was performed to evaluate the late complications of eye. Materials & Methods: In this descriptive study, 500 male patients (aged between 35 and 55), whose mustard gas injured period is more than 15 years were selected by non probability sampling. The patients were examined by an ophthalmologist. The complications were divided in 3 grades, mild, moderate and severe. The data were analyzed by x2 and spearman correlation coefficient. Results: Out of 500 warfare patients, 48% aged 35-40, 82.2% once injured with mustard gas, 12.2% twice injured with mustard gas, 1.8% three times injured with mustard gas and 3.8% more then 3 times injured with mustard gas. The degrees of complications: 80% mild Eye Complications, 13.2% moderate Eye Complications and 6.8% sever Eye Complications. There were significant relationships between Eye Complications degrees with using the drugs, the times of injury and the times of hospitalization (P<0.05). Conclusion: Having reached the mentioned conclusions, it is recommended to perform more comprehensive study to evaluate the complications of the other parts: eye, lung, skin ... as well.